Incentive effects of fiscal rules on the finance minister's behaviour: Evidence from revenue projections in Swiss Cantons - Florian Chatagny (ETH Zurich, KOF Swiss Economic Institute, 2013)
Predicting available tax revenue accurately is a key step of fiscal policy. It has recently been shown that revenue prediction errors have a direct impact on fiscal deficits. In the current paper we explore the relationship between the ideology of the finance minister and tax revenue projection errors and assess how the stringency of fiscal rules does alter this relationship. We use a panel dataset on 26 Swiss cantons over the period 1980-2007 as well as a new dataset on 99 finance ministers at the cantonal level. We find a rather counter-intuitive positive relationship between the ideology of the finance minister and tax revenue projection errors in the sense that a more left wing finance minister produces relatively more conservative forecasts. We also find that fiscal rules reduce the effect of ideology on tax revenue projection errors. These results suggest that left wing finance ministers need to curb deficits relatively more in order to signal the same level of competence than a right wing finance minister to the voters. It also suggests that fiscal rules render the signal less informative to the voters and thereby reduce the incentive for left wing finance ministers to be more conservative in their projections.
Keywords: C23; H68; H71; 330; Ideology; Finance minister; Fiscal Rules; Tax Revenue Projections